PKM Pelatihan Persediaan Ekonomis Pada Kelompok Usaha Batu Bata Di Kelurahan Limbung Kecamatan Bajeng Kabupaten Gowa - Nurman Nurman; Chalid Imran Musa; Uhud Darmawan Natsir; Kristina Parisi; Zainal Ruma; Anwar Anwar (STIKes Ibnu Sina Ajibarang, 2023)
This Community Service Partner (PKM) is a small micro business of Brick. Knowledge about inventory management in the Brick business is still a fundamental weakness in meeting market demand, so that the price of Brick is relatively determined by the market. The purpose of this service is to motivate Brick business owners to have the knowledge and skills to be able to carry out proper inventory management as a support in developing their business. The method of implementation uses a combination of lecture and practice. Participants consist of Brick business owners in Bajeng District, Gowa Regency. The technique of implementing the activity consists of three stages starting from the preparation stage, the implementation stage, and the activity evaluation stage. The results of the training show that Brick business owners have difficulty managing the inventory of their business due to limited business capital. The finances used in business are still combined with finance for household needs. After the simulation is carried out, the participants can understand inventory management in the business. Furthermore, Brick business owners can know inventory management properly. Knowledge about inventory management is emphasized on Brick business owners because the productive life of Brick is only 5 months in one year, so inventory can be a strategy to increase operating profits. The limitation in this training is that the implementation method has not used mentoring techniques, so that knowledge about inventory management can be implemented in business activities.